The Aquatic WATSU® Therapy Program Improves the Quality of Life of an Adult Male with Autism Spectrum Disorder. A Case Report - Tufekcioglu Ertan; Arslan Duran; Konukman Ferman; Zagorski Tomasz; Batti Turki Al; Filiz Bijen; Sulaimani Mona F.; Keating Ingrid Eichberg; Erzeybek Mustafa Said; Yilmaz Elif Burcu (Sciendo, 2023)
The purpose of this single case study was to investigate the effects of the WATSU training program (WTP) on 21 years old male with an Autism Spectrum Disorder (ASD). This study used a high level of individual and structured interventions to improve the underperforming adaptive functioning areas like social and academic skills in ASD. The individualized intervention of WTP was completed in five days using critical verbal and bodily language, technical demonstration, taking turns, basic skills, and timely feedback in a social and sensory-isolated environment. The results were collected via in-training observation, semi-structured family and athletic trainer interviews to evaluate the participant's condition before and after the WTP. The structured communication opportunities improved the sense of trust and played a prominent role in the development of the quality of life. The results indicated that WTP reduced repetitive movements, stress reactions, challenging behaviors, and improved communication skills. In addition, changing roles, positions, and transitions in WATSU training increased the participant's resiliency in his life with more comfort. Finally, tactile-emotional quality afferents, warmth, and buoyancy of the water, altered and enriched proprioceptive and vestibular input, being safely cradled in the arms instructor were likely to be the other factors improving the underperforming areas including communication, repetitive movements, stress reactions and challenging behaviors.